2018
DOI: 10.5830/cvja-2018-003
|View full text |Cite
|
Sign up to set email alerts
|

HIV disease is associated with increased biomarkers of endothelial dysfunction despite viral suppression on long-term antiretroviral therapy in Botswana

Abstract: SummaryBackgroundUntreated HIV infection is associated with increased biomarkers of endothelial dysfunction. However, the predictors and degree of endothelial dysfunction among virally suppressed HIV–infected adults on long–term antiretroviral therapy (ART) have not been well studied in sub– Saharan Africa (SSA). MethodsWe enrolled 112 HIV–infected adults with virological suppression on long–term ART and 84 HIV–uninfected controls in Botswana. We measured plasma levels of markers of endothelial injury [soluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 34 publications
3
35
1
Order By: Relevance
“…Our study is the largest to evaluate endothelial activation among PWH on ART and HIV-negative adults in Africa. It builds upon prior work from Kenya [ 43 ], Botswana [ 40 ], South Africa [ 22 ], and the United States and Europe that reported persistent endothelial activation markers in the ART era [ 44–47 ]. However, our findings are in contrast to a US-based study that demonstrated normalization of these markers after 12 months of ART [ 18 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our study is the largest to evaluate endothelial activation among PWH on ART and HIV-negative adults in Africa. It builds upon prior work from Kenya [ 43 ], Botswana [ 40 ], South Africa [ 22 ], and the United States and Europe that reported persistent endothelial activation markers in the ART era [ 44–47 ]. However, our findings are in contrast to a US-based study that demonstrated normalization of these markers after 12 months of ART [ 18 ].…”
Section: Discussionmentioning
confidence: 98%
“…Compared with Europe/US-based studies, the few studies looking at the association between immune activation and endothelial dysfunction conducted in African countries have been relatively small, have not directly evaluated the contribution of risk due to metabolic abnormalities vs HIV-associated inflammation/immune activation, and have not compared people with HIV with HIV-negative individuals. This comparison may be particularly relevant in developing countries, where all adults regardless of HIV status are at risk for inflammation and immune activation due to chronic exposure to bacterial and parasitic infections [ 40 ]. For these reasons, we believe that understanding these complex relationships in the presence of these exposures will be essential to understanding the pathophysiology of CVD in this setting.…”
mentioning
confidence: 99%
“…Recently, it has been shown by Grund et al that IL-6 and D-Dimer are independently associated with non-AIDS co-morbidities in PLWH, suggesting that treatment aiming to decrease these biomarkers may help to reduce morbidity and mortality in PLWH under ART [37]. It has also been shown that intercellular adhesion molecule (ICAM)-1, vascular cell adhesion molecule (VCAM)-1 and D-dimer, markers of CVDs [38,39,40], and monocyte chemotactic protein osteopontin (OPN), related to the risk of dementia, are elevated in PLWH [41].…”
Section: How Hiv Infection Impacts Microbiota Composition Chronicmentioning
confidence: 99%
“…The most commonly measured biomarkers included IL-6 [29, 53, 56, 97–108], highly sensitive CRP [7, 28, 98, 99, 101–104, 106, 108, 109] and D-dimer levels [7, 28, 98, 99, 101–104, 106, 108, 109]. In addition, a number of studies measured markers of endothelial adhesion or activation, or both, including soluble intercellular adhesion molecule-1 and soluble vascular cell adhesion molecule-1 [7, 15, 17, 50, 97, 106–108, 110–112], monocyte activation (sCD163, sCD14, or changes in monocyte phenotype) [15, 28, 29, 50, 56, 96, 97, 100, 107–114], and platelet activation (expression of s- and p-selectin) [30, 33, 115]. Limitations exist in many studies examining biomarkers for CVD outcomes.…”
Section: Pathophysiological Mechanisms Associated With Development Ofmentioning
confidence: 99%